Carbon capture and storage and the sustainable development goals. (June 2021) - Mikunda, Tom; Brunner, Logan; Skylogianni, Eirini; Monteiro, Juliana; Rycroft, Lydia; Kemper, Jasmin
Highlights: Carbon capture and storage can help achieve the sustainable development goals. It is a key enabler of goal 13 relating to combating climate change. It also enables provision of affordable energy and decarbonisation of industry. The capturing process has both positive and negative interactions with most sustainability goals. Abstract: For carbon capture and storage (CCS) to be a truly effective option within the efforts being made to mitigate climate change, it must be sustainable. An assessment is therefore required regarding how the deployment of CCS will positively contribute towards the achievement of the UN's Sustainable Development Goals (SDGs) by 2030. This assessment reviews current evidence regarding the interactions between CCS technologies and the SDGs to improve the accessibility of information regarding the relevance and sustainability of CCS as a climate mitigation technology. Implicit in the SDG logic is that the goals depend on each other and enablers for one goal may therefore also potentially act as inhibiters for another goal. When evaluated against the SDGs, CCS shows several positive 'enabling' interactions, and fundamentally CCS is 'indivisible' with SDG 13 regarding combating climate change. The main 'inhibiting' impacts are predominantly due to the requirement for extra energy per unit of electricity produced and the environmental impacts associated with the use of some capture systems. None of the inhibiting impacts identified had 'cancelling' interactions against the SDGs covered in this assessment. CCS is therefore a sustainable option to combat climate change and does not prohibit the achievement of any other SDG.